2009
DOI: 10.1542/peds.2009-1100e
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequality and Racial Discrimination: Risk Factors for Health Disparities in Children of Color

Abstract: A child's sense of control over life and health outcomes as well as perceptions of the world as fair, equal, and just are significantly influenced by his or her social experiences and environment. Unfortunately, the social environment for many children of color includes personal and family experiences of racial discrimination that foster perceptions of powerlessness, inequality, and injustice. In turn, these perceptions may influence child health outcomes and disparities by affecting biological functioning (eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
133
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(146 citation statements)
references
References 147 publications
11
133
1
1
Order By: Relevance
“…It is described as a period during which both positive investments and toxic stressors may significantly alter the trajectory of a child's life; 19 racism itself has been considered a toxic stressor. 20 Sanders-Phillips and colleagues 21 describe a conceptual model relating racial discrimination to child health disparities. This early time period has typically not been the focus of racial socialization studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is described as a period during which both positive investments and toxic stressors may significantly alter the trajectory of a child's life; 19 racism itself has been considered a toxic stressor. 20 Sanders-Phillips and colleagues 21 describe a conceptual model relating racial discrimination to child health disparities. This early time period has typically not been the focus of racial socialization studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, research has shown that clinically relevant stress-related biomarkers are higher in black than in white people, and these racial differences are not explained by SES. [42][43][44][45] For children and adolescents, discrimination related to race, ethnicity, or SES may affect the child directly. Timing of exposure to discrimination may alter its influence, with adolescents having the greatest likelihood of understanding the nature and meaning of discriminatory remarks and actions of others.…”
Section: Racial and Other Forms Of Discriminationmentioning
confidence: 99%
“…Nevertheless, a relatively small amount of research has examined health effects of discrimination for children and adolescents. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] This work, which has primarily focused on Black youth, has shown relationships between discrimination and greater externalizing symptoms (i.e., problem behaviors), 9,10,16,19,20 internalizing symptoms (anxiety, depression), 9,11,14,15,[21][22][23][24] and substance use. 12,13 Little is known regarding whether Latino youth similarly experience mental health deficits following discrimination.…”
Section: Introductionmentioning
confidence: 99%